2017
DOI: 10.1039/c7ay00516d
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the amine value in aliphatic amine epoxy hardeners by using a reaction-based headspace gas chromatographic technique

Abstract: This work investigates a reaction-based and solvent-assisted HS-GC method for the determination of the amine value in aliphatic amine epoxy hardeners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…[17][18][19] Headspace GC (HS-GC) has also been previously applied for the analysis of volatile amines in various sample matrices, due to its simplicity, ease of operation, and analytical performance in both research and quality control environments. For example, Xie et al 20 reported an automated strategy to quantify aliphatic amines in epoxy hardeners using reaction-based HS-GC. 20 Raghuram et al 12 successfully applied HS-GC for determining diethylamine (DEA) and triethylamine (TEA) in two APIs, and improved amine recovery by adding sodium hydroxide to the headspace sample solution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19] Headspace GC (HS-GC) has also been previously applied for the analysis of volatile amines in various sample matrices, due to its simplicity, ease of operation, and analytical performance in both research and quality control environments. For example, Xie et al 20 reported an automated strategy to quantify aliphatic amines in epoxy hardeners using reaction-based HS-GC. 20 Raghuram et al 12 successfully applied HS-GC for determining diethylamine (DEA) and triethylamine (TEA) in two APIs, and improved amine recovery by adding sodium hydroxide to the headspace sample solution.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Xie et al 20 reported an automated strategy to quantify aliphatic amines in epoxy hardeners using reaction-based HS-GC. 20 Raghuram et al 12 successfully applied HS-GC for determining diethylamine (DEA) and triethylamine (TEA) in two APIs, and improved amine recovery by adding sodium hydroxide to the headspace sample solution. 12 Although there have been diverse approaches to quantifying volatile amines, the analysis of these compounds in pharmaceutical entities presents an ongoing challenge for pharmaceutical scientists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Headspace gas chromatography (HS‐GC) is an efficient tool for the indirect analysis of nonvolatile chemicals that could be converted to some volatile substances based on some chemical reactions [14–18]. HS‐GC also can perform an in situ measurement at a precisely controlled temperature, and the headspace vial can be used as a small‐scale reactor to conduct chemical reactions and to monitor and quantify the generated gas products using HS‐GC.…”
Section: Introductionmentioning
confidence: 99%